TOWARDS A MORE COMPREHENSIVE UNDERSTANDING OF FOSTERING CONNECTIONS: THE TRAUMA-INFORMED FOSTER CARE PROGRAMME: A MIXED METHODS APPROACH WITH DATA INTEGRATION - Lotty, Maria; Bantry-White, Eleanor; Dunn-Galvin, Audrey (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
Foster carers require high-quality training to support them in caring for children with trauma-related difficulties. This paper describes a mixed methods approach that was applied to evaluate the complex intervention Fostering Connections: The Trauma-Informed Foster Care Programme, a recently developed trauma-informed psychoeducational intervention for foster carers in Ireland. A quantitative outcome evaluation and a qualitative process evaluation were integrated to capture a comprehensive understanding of the effects of this complex intervention. A convergent mixed methods model with data integration was used. Coding matrix methods were employed to integrate data. There was convergence among component studies for: programme acceptability, increased trauma-informed foster caring, improvement in child regulation and peer problems, and the need for ongoing support for foster carers. This research provides support for the intervention suggesting the importance of its implementation in Ireland. The integrative findings are discussed in relation to effects and future implementation.